Mannan-Binding Lectin Attenuates Inflammatory Arthritis Through the Suppression of Osteoclastogenesis - Dong, Lijun; Wu, Jun; Chen, Kai; Xie, Jingwen; Wang, Youyi; Li, Dantong; Liu, Yunzhi; Yin, Aiping; Zhao, Yue; Han, Yunpeng; Zhou, Jia; Zhang, Liyun; et al. (Frontiers in Immunology, 2019)
Mannan-binding lectin (MBL) is a vital element in the host innate immune system, which is primarily produced by the liver and secreted into the circulation. Low serum level of MBL is reported to be associated with an increased risk of arthritis. However, the underlying mechanism by which MBL contributes to the pathogenesis of arthritis is poorly understood. In this study, we investigated the precise role of MBL on the course of experimental murine adjuvant-induced arthritis (AIA). MBL-deficient (MBL−/−) AIA mice showed significantly increased inflammatory responses compared with wild-type C57BL/6 AIA mice, including exacerbated cartilage damage, enhanced histopathological features and high level of tartrate-resistant acid phosphatase (TRAP)-positive cells. MBL protein markedly inhibited the osteoclast formation from human blood monocytes induced by receptor activator of nuclear factor-κB ligand (RANKL) and macrophage colony-stimulating factor (M-CSF) in vitro. Mechanistic studies established that MBL inhibited osteoclast differentiation via down-regulation of p38 signaling pathway and subsequent nuclear translocation of c-fos as well as activation of nuclear factor of activated T-cells c1 (NFATc1) pathway. Importantly, we have provided the evidence that concentrations of MBL correlated negatively with the serum levels of amino-terminal propeptide of type I procollagen (PINP) and C-terminal telopeptide of type I collagen (β-CTX), serum markers of bone turnover, in patients with arthritis. Our study revealed an unexpected function of MBL in osteoclastogenesis, thus providing new insight into inflammatory arthritis and other bone-related diseases in patients with MBL deficiency.